Bilateral central scotomata due to intracranial tumour. Issue 7 (July 1984) - Page, N G; Sanders, M D
Abstract : Bilateral centrocaecal scotomata have been recognised as a sign of intrinsic optic nerve disease, usually associated with hereditary optic neuropathy, and nutritional or toxic amblyopias. This report describes four patients with central scotomata due to intracranial masses, three of whom recovered after surgical intervention. The clinician should be alerted to the association in patients with headaches, other neurological signs, and central visual loss.